ANALYZING THE IMPACT OF INDIAN STOCK MARKET DEVELOPMENTS ON THE BEHAVIORAL PATTERNS OF RETAIL INVESTORS IN THE NORTH COASTAL REGION OF ANDHRA PRADESH - INVESTIGATING THE DYNAMICS OF THE SECONDARY MARKET - Rao Challa, Trinadha (International Journal of Psychosocial Rehabilitation, 2019)
A stock exchange is a market which facilitates buying and selling of shares, stocks, bonds, securities and debentures. It is not only a market for old securities and shares but also for new issues shares and securities. In fact, the capital market is related to the supply and demand for new capital, and the stock exchange facilitates such transactions.The liquidity that an exchange provides affords investors the ability to sell securities quickly and easily. It plays a crucial role in the financial system. It is considered as one of the best ways to increase the funds. But before any investor make any investment into stock market; investor should know how to get started. It may turn out to be a profitable affair as long as we know the tricks of the trade